A synthesis of academic literature on eco-spirituality - A.H.A. Adow; M.M. Safeer; M.G.H. Mohammed; M. Sayeed Alam; M.M. Sulphey (Global Journal of Environmental Science and Management)
This study critically examines the concept of eco-spirituality, exploring its intersection with spirituality and environmental concerns and its profound implications for contemporary society. The objective of this study is to systematically analyze the expanding literature on eco-spirituality and environmental behavior, highlighting key influencers, seminal works, and emerging trends to provide a comprehensive overview and suggest future research directions. Drawing from a synthesis of 138 studies, the research sheds light on the transformative role of eco-spirituality in facilitating the transition towards environmental sustainability. A comprehensive analysis of scholarly publications reveals notable trends in eco-spirituality research. Despite emerging in the early 1990s, scholarly attention remained limited until the 21st century, witnessing a significant surge post-2019, indicating growing recognition within academia. Publications predominantly originated from the United States, the United Kingdom, Canada, India, and Switzerland, reflecting global interest and engagement across diverse cultural landscapes. Key journals, including Religions, emerged as prominent platforms, underscoring the interdisciplinary nature of eco-spirituality research. The study underscores the interdisciplinary nature of eco-spirituality, transcending disciplinary boundaries to incorporate insights from environmental studies, theology, psychology, sociology, anthropology, and philosophy. The synthesis of 138 studies reveals eco-spirituality's pivotal role in promoting environmental sustainability, with notable trends in scholarly interest and global distribution of publications. Scholarly attention to eco-spirituality surged post-2019, resulting in 74 published articles, with 2021 marking the peak at 15 articles and the United States contributing 38 publications. This study underscores the interdisciplinary nature of eco-spirituality research and its potential to bridge theoretical insights with practical applications, urging inclusive approaches and further exploration beyond academia. This study contributes to meaningful societal change through environmental education, community engagement, and policy development. While acknowledging limitations such as database constraints and language bias, the study offers a nuanced understanding of the multifaceted impacts of eco-spirituality on individuals and communities. It prompts further inquiry into the dynamic relationship between spirituality, environmental ethics, and sustainable development. The study also underscores the significance of eco-spirituality as a catalyst for environmental consciousness and sustainable action. The innovation of the study is that it has revealed eco-spirituality's transformative role in promoting environmental sustainability and bridging interdisciplinary insights with practical applications. By synthesizing existing evidence and highlighting avenues for future research, it contributes to ongoing discussions on the role of spirituality in shaping human interactions with the natural world, ultimately empowering individuals and communities to enact meaningful change and promote a more harmonious relationship with the planet.